Late Presentation of Arrhythmogenic Right Ventricular Cardiomyopathy : Role of Non Invasive Modalities for The Diagnosis - Sungkar, Safir; Nugroho, Mochamad Arif (RSUP Dr. Kariadi, 2019)
Background : Arrhythmogenic right ventricular cardiomyopathy(ARVC) is an inherited myocardial disease affecting predominantly young people and manifests as sustained ventricular tachycardia, sudden cardiac death (SCD) or heart failure. However, its first manifestation in older patients is infrequent. Diagnosis of ARVC remains a clinical challenge and need further investigation. Our case report investigated role of non invasive modalities for diagnosis of ARVC patient. Case Presentation : A 65 year old man was admitted to the hospital with symptoms of palpitationand near syncope. An Electrocardiogram (ECG) showed a sustained VT with LBBB morphology and inferior axis. The patient was cardioverted to sinus rhytm with a single 100J shock. Postcardioversion ECG showed an epsilon wave in right precordial leads. Echocardiography revealed extensive RV enlargement and reduce function. Our patient had three major (RV aneurysm, epsilon wave and T wave inversion) and one minor criteria (sustained LBBB type-VT with inferior axis)making the diagnosis of ARVC definite according to the revised Task Forced Criteria. Conclusion: ARVC may have a very late presentation and this diagnosis should be considered as a potential cause of sustained VT of RV origin among the elderly. ECG and echocardiography as non invasive modalities have an important role for the diagnosis of patients with suspected ARVC. Keywords :Arrhythmogenic right ventricular cardiomyopathy,ventricular tachycardia, sudden cardiac death, diagnosis.